Optimization of WSNs Flooding Rates by Khalimsky Topology - Abdellaoui, Mahmoud; Gargouri, Riyadh; Mezghani, Mahmoud (Discoveries in Agriculture and Food Sciences, 2015)
<!–[if gte mso 9]> <![endif]–> In this paper, we proposed a new method of deploying and building an organized architecture of gateway nodes in a Wireless Sensors Network (WSN) formed also by randomly deployed sensors arranged in clusters. This method, based on the Khalimsky theory, reduces the energy consumption and the flooding rates of the conventional flooding algorithm. Our solution allowed to build a hierarchical topology reduces the number of communication links between nodes while maintaining the adjacency list to minimize the data redundancy. It allows calculating an optimal set of forwarding gateway nodes to route data packets between a source and a destination. This set includes all optimal paths using the less number of nodes. Our simulation study shows that the Khalimsky theory reduces considerably the flooding rates and the energy consumption. <span style="font-size: 11.0pt; mso-bidi-font-size: 12.0pt; line-height: 115%; font-family: ’Calibri’,’sans-serif’; mso-fareast-font-family: SimSun; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold;" lang="EN-US">Our solution can be applied in the fields needing prefixed gateway nodes and randomly deployed sensors which use urgent data with real-time aspect such as the security and the monitoring of industrial zones and home building.<!–[if gte mso 9]> Normal 0 21 false false false FR X-NONE AR-SA <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>